(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2024)
Лотиш О.Я., Костецька Н.І. АДАПТАЦІЯ БІЗНЕС-МОДЕЛЕЙ РОЗВИТКУ ПІДПРИЄМСТВ АПК УКРАЇНИ ДО ЕКОНОМІЧНИХ ВИКЛИКІВ СУЧАСНОСТІ Мета. Аналіз стану АПК, обґрунтування вибору бізнес-моделей функціонування аграрних підприємств в Україні та їхня адаптація до викликів воєнного часу. Методика дослідження. Теоретичною і методологічною основою дослідження є наукові праці провідних вчених та підприємців-практиків на ринку АПК України. У процесі дослідження використано такі загальнонаукові методи: порівняння – для дослідження бізнес-моделей розвитку суб’єктів агропромислового комплексу; аналізу і синтезу – для аналізу стану розвитку підприємств АПК; абстрактно-логічний – для висловлювань власних припущень та формулювання висновків, графічний – для наочного ілюстрування динаміки розвитку, втрат і збитків галузей АПК. Результати дослідження. Узагальнено, що формування адаптаційної бізнес-моделі повинно враховувати внутрішні і зовнішні чинники функціонування агропідприємства в умовах воєнної агресії росії в Україні. Проаналізовано показники розвитку галузі рослинництва, як однієї із структуроформуючих в економіці країни, а також прямі збитки і непрямі втрати у рослинництві і тваринництві, спричинені війною. Виявлено, що особливістю агропромислового комплексу України є наявність в ньому значної частки агрохолдингів і фермерських та особистих господарств. Акцентовано на тому, що війна зумовила додаткові негативні аспекти функціонування агрохолдингової моделі українського АПК, зокрема розрив логістичних ланцюгів, екологічні катастрофи на тваринницьких комплексах агрохолдингів, блокування ринків збуту показали низьку адаптивність і неспроможність таких підприємств вчасно реагувати на виклики воєнного часу. Наукова новизна результатів дослідження. Набули подальшого розвитку особливості пристосування бізнес-моделей розвитку аграрних підприємств, враховуючи прямі збитки і непрямі втрати внаслідок російської агресії. Порівняння сучасних моделей функціонування АПК в Україні дало змогу визначити недоліки агрохолдингової моделі та запропонувати напрямки державної підтримки розвитку фермерської бізнес-моделі за умов сучасних викликів. Практична значущість результатів дослідження. Результати дослідження можуть бути використані для аналізу і адаптації бізнес моделей агропідприємств у воєнний і післявоєнний період. Ключові слова: агропромисловий комплекс, рослинництво, тваринництво, бізнес-модель, адаптація, фермерські господарства, агрохолдинги. Lotysh O.Ya., Kostetska N.I. ADAPTATION OF BUSINESS MODELS FOR THE DEVELOPMENT OF UKRAINIAN AGRICULTURAL ENTERPRISES TO THE CURRENT ECONOMIC CHALLENGES Purpose. The aim of the article is to analyse the state of the agro-industrial complex and substantiate the directions for the adaptation of business models for the development of agrarian enterprises in Ukraine during the military challenges. Methodology of research. The theoretical and methodological basis of the research is the scientific works of leading scientists and businessmen-practitioners in the agricultural sector of Ukraine. In the research process, the following general scientific methods were used: comparison method – for the study of business models of the development of subjects of the agro-industrial complex; analysis and synthesis – to analyse the state of development of agro-industrial complex enterprises; abstract and logical method – for expressing one’s own assumptions and formulating conclusions, graphic method – for visual illustration of the dynamics of the development, losses and damages of the agricultural sector. Findings. It was concluded that the formation of an adaptive business model should take into account both the internal and external factors of the functioning of an agricultural enterprise in conditions of Russia’s military aggression in Ukraine. The indicators of the development of the field of crop production, as one of the structural factors in the country’s economy, as well as direct losses and indirect losses in crop production and livestock production caused by the war, were analysed. It was found that a feature of the agro-industrial complex of Ukraine is the presence of a significant share of agricultural holdings and farms and personal farms in it. It was emphasized on the fact that the war had caused additional negative aspects of the functioning of the agroholding model of the Ukrainian agricultural industry, in particular, the breakdown of logistics chains, environmental disasters at the livestock complexes of agroholdings, the blocking of sales markets showed the low adaptability and inability of such enterprises to respond in time to the challenges of wartime. Originality. The features of business models adaptation for the development of agrarian enterprises, taking into account both direct and indirect losses due to Russian aggression, have gained further development. The comparison of the modern models of the functioning of the agro-industrial complex in Ukraine made it possible to identify the disadvantages of the agricultural holding model and to propose the directions for state support for the development of the farming business model in conditions of modern challenges. Practical value. The results of the study can be used for the analysis and adaptation of business models of agricultural enterprises in the war and post-war period. Key words: agro-industrial complex, plant breeding, livestock breeding, business model, adaptation, farms, agricultural holdings.